Value Engineering Building Structure Civil Servent Paspampres PUPR Precast with Lead Rubber Bearing Potential Fault Zone - Riyanto Rivky (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Life cycle cost (LCC) analysis is a method that can be used to control initial costs and future costs in investing in a project where in this case the use of Lead Rubber Bearing (LRB) technology. The purpose of this study is to analyze the economic value of a building by taking into account the cost of operating the building during the life cycle. Therefore, it is necessary to conduct a study on life cycle cost analysis to find out what costs are contained in the ASN Paspampres, IKN Flat Construction Project and to be able to find out how much costs are incurred starting from the design stage to the age of the building plan that has been determined. The data used are Plan Drawings, Cost Budget Plans (RAB) from the project and literature studies that support the research. The estimated cost of replacement and repair in the future is calculated on present value, with an economic life of building construction for 50 years with a simulation of an earthquake occurring only 1 time, assuming 6% interest, assuming an inflation rate of 2.61%, an increase in the price of construction materials and Lead Rubber Bearing (LRB) per year of 0.99%. Life Cycle Cost (LCC) analysis based on 4 system categories is that conventional LCC is greater than precast LCC, conventional LCC + LRB and precast LCC + LRB. Based on the value of Conventional LCC + LRB and Precast LCC + LRB is still more efficient than Conventional LCC and precast LCC, if the earthquake event is below the 12th year for Conventional LCC + LRB and the earthquake event is below 38 years for precast LCC + LRB. The deviation value between conventional LCC + LRB decreases over time until it approaches zero deviation (0) near the 12th year and after that year (12th) the deviation becomes negative. This means that after the 12th year Conventional LCC + LRB is already inefficient compared to Conventional LCC. The deviation value between Precast LCC + LRB decreases over time until it approaches zero deviation (0) near the 38th year and after that year (38th) the deviation becomes negative. This means that after the 38th year Precast LCC + LRB is no longer efficient compared to Conventional LCC.